Analysis of thinning programs application in the Leningrad region - Akaykin, Daniil (SLU/Southern Swedish Forest Research Centre, 2010)
This paper aims at investigating a possible applicability of a Swedish forest growth simulator “ProdMod” in conditions of North-West Russia. The result from ProdMod was based on materials from The Series of Stationary Experimental Objects and particularly section 1 “Development of Stands Not Touched By Silvicultural Activity”. Results of forecast by ProdMod are compared with stands development observed on sample plots. Basal area and volume development are two crucial parameters in the comparisons. ProdMod shows quite good results, but there are some dissimilarities in volume development. It is concluded that this program can be useful in conditions of North-West Russia, but still it requires some corrections. Possible successful thinning programs (from economic point of view) are evaluated. The 6 thinning programs with different intensities and frequencies of thinning were investigated in stands with different tree species composition. The program with “flexible” thinning schedule for each stand shows the highest results incase of NPV. There isn’t a universal program, which shows only highest results for all parameters. Each program has its strong and weak sides. Despite good results, some of successful thinning programs can hardly be applied in North-West Russia due to the features of Russian forest sector and thinning rules.